ANALYSIS AND RECOMMENDATIONS FOR MAINTENANCE SCHEDULING OF OUTDOOR SIGNALING EQUIPMENT ON AUTONOMOUS TRAINS LRT JABODEBEK - Dwi Raharjo, Rachmad
The signaling system used in Jabodebek LRT is the Communication Based Train Control (CBTC) Grade of Automation (GoA) level 3 system, which is a moving block and autonomous train system. The CBTC GoA 3 signaling system of Jabodebek LRT has a complex system with several types of new equipment and is different from the existing trains in PT Kereta Api Indonesia (Persero). This system was first implemented in Indonesia, so to ensure the safety of train operations, optimal preventive maintenance is needed on the signaling equipment. The purpose of this research is to evaluate the maintenance program that has been implemented and design an effective preventive maintenance scheduling, by optimizing resources and overcoming operational obstacles.